Buckling response of composite cylindrical shells with various stiffener layouts under uniaxial compressive loading. (October 2021) - Rafiee, Mojtaba; Hejazi, Mehrdad; Amoushahi, Hossein
Highlights: Buckling analysis of stiffened cylindrical GFRP shells with arbitrary stiffeners by the curved finite strip method. Koiter's theory and the first-order shear deformation theory were used for curved finite strip formulation. The stiffeners can be placed everywhere on the inner and the outer surfaces of the shell independent of nodal lines. The number of elements and time consumed for analysis are much less than the conventional finite element method. Eccentricity, torsional stiffness, and stiffening scheme of stiffeners increase the buckling load coefficient. Abstract: This research presents a study on the buckling behaviour of the stiffened cylindrical shells made of laminated glass fibre-reinforced polymer (GFRP) with arbitrary stiffeners under axial compression by using the curved finite strip method. The stiffeners can be positioned at the inner and outer surfaces of the shell, and is no need to be located on the nodal lines. The governing equations of motion are extracted from Koiter's theory based on the first-order shear deformation theory and solved employing the principle of the minimum potential energy. Then, both the critical buckling load and the buckling load coefficient are calculated by solving characteristic equations. Boundary conditions considered are simple-simple, clamped–clamped, and clamped-simple supports. A relatively high-order polynomial function for the displacement components in the transverse direction is assumed for the shell and the stiffeners. A displacement model is assumed with twenty-four degrees of freedom arranged at four nodal lines for each strip. To validating the proposed method, the results of this investigation are compared with the finite element, experimental and other published numerical results. The benefits of this method are that number of elements, and therefore time consumed for analysis is much less, and the mesh refinement process is much more convenient than the conventional finite element method. Finally, the effects of the different parameters such as Poisson's ratio, boundary condition, thickness variations and geometrical parameters of shell and stiffeners, angle, eccentricity, torsional stiffness, cross-sectional area, number of stiffeners on the buckling are studied. The results obtained can be employed as a significant benchmark for researchers to verify their analytical and numerical approaches.